Senior change leaders' reaction to change: a grounded theory approach - Uprety, Artiom (IE University, 2021)
Little is known about how senior change leaders (SCLs) experience the changes they are leading. The organizational change literature has largely focused on the reaction to change by change recipients, while empirical research on change agents’ reactions targets mid-managers responsible for implementing change initiated by others. This qualitative study uses an interpretative grounded theory approach to develop a model of SCLs’ reactions while leading planned organizational transformations by analyzing retrospective interviews with 32 SCLs in a wide range of geographies, industries and change contexts. The findings reveal that SCLs perceive their roles to be emotionally, mentally and physically demanding and therefore stressful; however, the type of stress they experience depends on their appraisal of their situation regarding their perception of the valence of the change, the specific demands of the role and the resources available to address these demands. If SCLs appraise their situation positively, they experience challenge stress and the associated positive emotions, causing them to be more effective. If this positive appraisal is sustained, SCLs may enter self-reinforcing ‘gain loops’ of further effective behavior, achievements and resource gains. However, if SCLs appraise their situation negatively, they experience hindrance stress, causing them to be ineffective; and if this negative appraisal is sustained, SCLs can enter self-reinforcing ‘doom loops’. SCLs are constantly reappraising their situation as their role, resources and the valence of the change evolves, and as a result they can temporarily shift from challenge to hindrance stress (or vice-versa). If the factors causing the shift are sustained, however, leaders may break the doom loop to enter the gain loop (or vice-versa). The emergent process model offers a theoretically integrated approach to the study of change leadership and practical insights that may help to increase the success rate of organizational transformation programs.
La economía informal suele estar poco estudiada, por lo que carecemos de una comprensión conceptual sobre cómo compiten y elaboran estrategias las empresas en la parte ilegal de la economía. En esta tesis, trato de corregir esta situación examinando las estrategias que utilizan las farmacias ilegales online que atienden al mercado estadounidense, así como sus grupos de interés, para ayudar a dilucidar las teorías generales de gestión a través de tres ensayos empíricos. En el primer ensayo examino cómo responde el público al uso de múltiples esfuerzos de gestión de la impresión, y muestro que en un determinado momento añadir esfuerzos puede ser perjudicial porque puede surgir la sospecha. Esto subraya la importancia de explorar la reflexión cuando se estudia la gestión de la impresión. En el segundo ensayo ofrezco una novedosa justificación de por qué algunas certificaciones pueden ser perjudiciales para la empresa, examinando los incumplimientos de las expectativas del público. Demuestro que si el público cree que los problemas son importantes en una empresa, las certificaciones se ven como una forma de mostrar que esos problemas se están abordando, lo que da lugar a un incumplimiento positivo de las expectativas y a una mejora de los resultados de la confianza. Si, por el contrario, el problema no se considera significativo, las certificaciones informan de que el problema es más importante de lo que se esperaba en un principio, lo que da lugar a un incumplimiento negativo de las expectativas y a peores resultados de confianza. En el tercer ensayo construyo un modelo más matizado sobre a quién se dirigen los organismos de control. Sostengo que es menos probable que los organismos de control se dirijan a los infractores con fuertes ventajas competitivas y recursos/capacidades difíciles de crear, porque es más probable que los ignoren dado lo mucho que perderían, y por lo tanto son relativamente más costosos de perseguir. Mi tesis contribuye a una serie de teorías de gestión, como la gestión de las impresiones, la certificación, los incumplimientos de las expectativas y las teorías de cumplimiento de las leyes.
Keywords: Leadership; Organizational change; Reaction to change; Grounded theory; Estudio de Mercado; Comportamiento del Consumidor; 1207.02 Sistemas de Control